0D/2D Heterojunctions of Vanadate Quantum Dots/Graphitic Carbon Nitride Nanosheets for Enhanced Visible‐Light‐Driven Photocatalysis - Ye, Meng‐Yang; Zhao, Zhi‐Hao; Hu, Zhuo‐Feng; Liu, Le‐Quan; Ji, Hui‐Ming; Shen, Zhu‐Rui; Ma, Tian‐Yi (Angewandte Chemie International Edition, 2017)
0D/2D heterojunctions, especially quantum dots (QDs)/nanosheets (NSs) have attracted significant attention for use of photoexcited electrons/holes due to their high charge mobility. Herein, unprecedent heterojunctions of vanadate (AgVO3, BiVO4, InVO4 and CuV2O6) QDs/graphitic carbon nitride (g‐C3N4) NSs exhibiting multiple unique advances beyond traditional 0D/2D composites have been developed. The photoactive contribution, up‐conversion absorption, and nitrogen coordinating sites of g‐C3N4 NSs, highly dispersed vanadate nanocrystals, as well as the strong coupling and band alignment between them lead to superior visible‐light‐driven photoelectrochemical (PEC) and photocatalytic performance, competing with the best reported photocatalysts. This work is expected to provide a new concept to construct multifunctional 0D/2D nanocomposites for a large variety of opto‐electronic applications, not limited in photocatalysis. Vanadate quantum dots including AgVO3, BiVO4, InVO4, and CuV2O6 were strongly coupled with graphitic carbon nitride nanosheets using an in situ growth strategy. These quantum dots displayed a much better visible‐light‐driven photoelectrochemical activity and photocatalytic degradation efficiency than single vanadate quantum dots, carbon nitride nanosheets or previously reported highly active photocatalysts.